Archive-se! História, documentos e memória arquivística no Ceará (1835-1934) - Fernandes, Ana Carla Sabino (2012)
This thesis discusses the historical trajectory of the archivistical formation in Ceará, with the institution of the Archive of the Secretariat of the Province of Ceará Government (1835) and the creation of the Public Archives of the State of Ceará (1932). I analyze the practices of documentary accumulation and the archiving operations filed by the provincial presidents and experienced by the public employees who worked in the Secretariat and / or in the Archive of the provincial government. That is, the operating system of this type of Archive on the need for meaning, throug archivistical theory, the diplomatic and public law, the archive file as evidence and testimony of the processes of governance of the Brazilian Empire, including the actions of gathering documents in the province of Ceará by the Public Archives of Empire (1838) and political doings of the executive power of the court in Rio de Janeiro and the Province of Ceará. Establishing, for both, intense dialogue with the histociral guidelines, policies and archival of Eusebio de Sousa (1883-1947), director of the Public Archives of State of Ceará between 1932-1942, notably those achievements and the directions that have dated and legalized the archival tradition and the Archive in Ceará form 1932, under the influence of historical studies of the Historical, Geographical and Anthropological Institute of Ceará (1887) and the paradigms that governed the Public Archives in the twentieth century as a "place" of memory and historical document. The theoretical framework of this investigatino is guided by reseraches and concepts of the social history of memory and cultural history, especially the linkages of significance between historical and archuivistical memory in establishing the relationship between history, archive and document. The sources were, in most cases, the documentary funds of/about the Public Archives, Reports of Presidents of the Province and Provincial Legislation and the State of Ceará.